A human bone infection organ model for biomaterial research. (May 2022) - Kuehling, Theodor; Schilling, Pia; Bernstein, Anke; Mayr, Hermann O.; Serr, Annerose; Wittmer, Annette; Bohner, Marc; Seidenstuecker, Michael
Abstract: The aim of this work was to establish an organ model for staphylococcal infection of human bone samples and to investigate the influence and efficacy of a microporous β-tricalcium phosphate ceramic (β-TCP, RMS Foundation) loaded with hydrogels (alginate, alginate-di-aldehyde (ADA)-gelatin) and clindamycin on infected human bone tissue over a period of 28 days. For this purpose, human tibia plateaus, collected during total knee replacement surgery, were used as a source of bone material. Samples were infected with S. aureus ATCC29213 and treated with differently loaded β-TCP composites (alginate +/- clindamycin, ADA-gelatin +/- clindamycin, unloaded). The loading of the composites was carried out by means of a flow chamber. The infection was observed for 28 days, quantifying bacteria in the medium and the osseus material on day 1, 7, 14, 21 and 28. All samples were histologically processed for bone vitality evaluation. Bone infection could be consistently performed within the organ model. In addition, a strong reduction in bacterial counts was recorded in the groups treated with ADA-gelatin + clindamycin and alginate + clindamycin, while the bacterial count in the control groups remained constant. No significant differences between groups could be observed in the number of lacunae filled with osteocytes suggesting no differences in bone vitality among groups. In an ex-vivo human bone infection model, over a period of 28 days bacterial growth could be reduced by treatment with ADA-Gel + CLI and ALG + CLI -releasing β-TCP composites. This could be relevant for its clinical use. Further work will be necessary to improve the loading of β-TCP and the bone infection organ model itself. Statement of Significance: The common treatment of bone infections is debridement and systemic administration of antibiotics. In some cases, antibiotic-containing carriers are already used, but these must be removed again. Our work is intended to show another treatment option. The scaffold we have developed, made of a calcium phosphate ceramic and a hydrogel as the active substance carrier, can, in addition to releasing the active substance, also assume a load-bearing function of the bone and is biodegradable. In addition, the model we developed can also be used for the analysis and treatment of bone infections other than those of the musculoskeletal system. More importantly, it can also serve as a substitute for previously used animal experiments. Graphical abstract: Image, graphical abstract